IMPLEMENTASI KEGIATAN EKSTRAKURIKULER KARAWITAN DALAM MENINGKATKAN NILAI CINTA BUDAYA LOKAL PADA SISWA SD NEGERI MANYARAN 01 - Desva Firantinur; Eka Titi Andaryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The preservation of local culture through education is crucial amid the rise of globalization, which has led to a decline in the younger generation’s interest in traditional arts, including karawitan. Elementary school students tend to be more interested in modern culture; therefore, efforts are needed to instill a love for local culture from an early age through culture-based extracurricular activities. This study aims to describe the implementation of karawitan extracurricular activities, analyze their role in fostering a love for local culture among students, and identify the factors supporting their implementation at Manyaran 01 Public Elementary School. The study employs a qualitative approach, specifically a descriptive qualitative study and a case study. Data collection was conducted through observation, interviews, and documentation, with research subjects including students participating in the karawitan extracurricular activity, the instructor, and the school principal. Data analysis was performed using the Miles and Huberman model, which includes the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the karawitan extracurricular activities are running smoothly and have a positive impact on students’ artistic skills, character development, and an increased appreciation for local culture through the values of discipline, cooperation, responsibility, and pride in regional culture.